FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2016 - Sigit Nugroho, 14.05.52.0233; Sudiyatno, Bambang (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the effect of profitability (ROE), sales growth, asset structure, liquidity, business and business risk on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2016 period. The sampling method used was purposive sampling, with 150 data processed. The analytical tool used is multiple regression analysis. The test hypothesis used t-statistics and f-statistics at a significant level of 5%. The results of this study indicate that liquidity has a significant negative effect on the capital structure, while profitability (ROE), sales growth, asset structure, tax and business risk do not affect the capital structure. Keywords: ROE, sales growth, asset structure, liquidity, tax and business risk